An improvement in skeletal muscle mitochondrial capacity with short‐term aerobic training is associated with changes in Tribbles 1 expression. Issue 12 (19th June 2020) - Vega, Rick B.; Brouwers, Bram; Parsons, Stephanie A.; Stephens, Natalie A.; Pino, Maria F.; Hodges, Andrew; Yi, Fanchao; Yu, Gongxin; Pratley, Richard E.; Smith, Steven R.; Sparks, Lauren M.
Abstract: Exercise training and physical activity are known to be associated with high mitochondrial content and oxidative capacity in skeletal muscle. Metabolic diseases including obesity and insulin resistance are associated with low mitochondrial capacity in skeletal muscle. Certain transcriptional factors such as PGC‐1α are known to mediate the exercise response; however, the precise molecular mechanisms involved in the adaptation to exercise are not completely understood. We performed multiple measurements of mitochondrial capacity both in vivo and ex vivo in lean or overweight individuals before and after an 18‐day aerobic exercise training regimen. These results were compared to lean, active individuals. Aerobic training in these individuals resulted in a marked increase in mitochondrial oxidative respiratory capacity without an appreciable increase in mitochondrial content. These adaptations were associated with robust transcriptome changes. This work also identifies the Tribbles pseudokinase 1, TRIB1, as a potential mediator of the exercise response in human skeletal muscle. Abstract : An 18‐day aerobic exercise training regimen increased skeletal muscle mitochondrial capacity and Tribbles 1 expression. These adaptations were associated with robust transcriptome changes. This work also identifies the Tribbles pseudokinase 1, TRIB1, as a potential mediator of the exercise response in human skeletal muscle.